Synthesis and Characterization of Zeolite X from Boiler Ash and Aluminum Foil Waste - Intan Ayu Safitri; Iis Siti Jahro (Universitas Negeri Medan, 2021)
This study aims to determine the effect of the Si/Al molar ratio and the number of Na2EDTA additions on the purity and crystallinity levels of the synthesized zeolite X. zeolite X was synthesized by hydrothermal method at 70°C and 120°C for 3 and 6 hours, respectively. In the synthesis of zeolite X used boiler ash and aluminum foil waste. The results of characterization using Fourier Transform Infra Red (FT-IR) and X-Ray Diffraction (XRD) showed that the level of purity and crystallinity of the synthesized zeolite X was influenced by the variation of Si/Al molar rasio and amount of Na2EDTA addition. The zeolite with the best quality was obtained from the synthesis with a Si/Al molar ratio of 1.6 and the amount of Na2EDTA added as much as 3.0 g. The synthesized zeolite X has a purity level of 75% and a degree of crystallinity with a total intensity of 845.